Molecular Screening for Nigericin Treatment in Pancreatic Cancer by High-Throughput RNA Sequencing - Xu, Zhihua; Gao, Guanzhuang; Liu, Fei; Han, Ye; Dai, Chen; Wang, Sentai; Wei, Guobang; Kuang, Yuting; Wan, Daiwei; Zhi, Qiaoming; Xu, Ye (Frontiers in Oncology, 2020)
Objectives: Nigericin, an antibiotic derived from Streptomyces hygroscopicus, has been proved to exhibit promising anti-cancer effects on a variety of cancers. Our previous study investigated the potential anti-cancer properties in pancreatic cancer (PC), and demonstrated that nigericin could inhibit the cell viabilities in concentration- and time-dependent manners via differentially expressed circular RNAs (circRNAs). However, the knowledge of nigericin associated with long non-coding RNA (lncRNA) and mRNA in pancreatic cancer (PC) has not been studied. This study is to elucidate the underlying mechanism from the perspective of lncRNA and mRNA. Methods: The continuously varying molecules (lncRNAs and mRNAs) were comprehensively screened by high-throughput RNA sequencing. Results: Our data showed that 76 lncRNAs and 172 mRNAs were common differentially expressed in the nigericin anti-cancer process. Subsequently, the bioinformatics analyses, including Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, coding and non-coding co-expression network, cis- and trans-regulation predictions and protein-protein interaction (PPI) network, were applied to annotate the potential regulatory mechanisms among these coding and non-coding RNAs during the nigericin anti-cancer process. Conclusions: These findings provided new insight into the molecular mechanism of nigericin toward cancer cells, and suggested a possible clinical application in PC.